2018
DOI: 10.25301/jpda.274.195
|View full text |Cite
|
Sign up to set email alerts
|

Parental Influence on Early Childhood Caries

Abstract: Parents have a significant role in educating their children about oral hygiene, therefore their knowledge and attitude influences their children oral health status. METHODOLOGY: In this cross-sectional study questionnaires were distributed to 300 mothers from Dow Dental College OPD to assess their knowledge, attitude and practice towards their children oral health. Questionnaire assessed demographic data, literacy level, importance of primary dentition and aspects of early childhood decay. Data was analyzed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…This sentiment was found in a recent study where 30% of parents with a postgraduate level of education similarly felt that treatment on deciduous teeth would be unnecessary since the teeth would exfoliate on their own and be replaced by a permanent tooth (Srinivas & Jeevanandan, 2019). However, studies have found that 56.3% of mothers were cognizant of the importance of keeping the deciduous teeth in good health (Faheem, Maqsood, & Shaikh, 2018). This research seeks to answer the following question: What is the relationship between a parent's level of oral hygiene knowledge and their child's oral hygiene behaviors in the greater United States?…”
Section: Introductionmentioning
confidence: 99%
“…This sentiment was found in a recent study where 30% of parents with a postgraduate level of education similarly felt that treatment on deciduous teeth would be unnecessary since the teeth would exfoliate on their own and be replaced by a permanent tooth (Srinivas & Jeevanandan, 2019). However, studies have found that 56.3% of mothers were cognizant of the importance of keeping the deciduous teeth in good health (Faheem, Maqsood, & Shaikh, 2018). This research seeks to answer the following question: What is the relationship between a parent's level of oral hygiene knowledge and their child's oral hygiene behaviors in the greater United States?…”
Section: Introductionmentioning
confidence: 99%